Examining the Antibiotic Resistance Pattern of Escherichia Coli Isolates Obtained from Patients Referred to the Central Laboratory of Meibod City in 2021 - Hamid Reza Talebi; Jamshid Ayatollahi; Zohra Akhundi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: The indiscriminate use of antibiotics causes the increasing trend of microbial resistance, followed by the limitation of treatment options, complicated treatment processes, and heightened expenses within the healthcare system. In this study،, it was investigated the antibiotic resistance of Escherichia coli obtained from urine culture samples in the central laboratory of Meybod City. Methods: This descriptive cross-sectional study was conducted on urine cultures submitted by the patients referred to the central laboratory of Meibod City in 2022. Antibiotic resistance in 300 E. coli cultures was investigated, and the data were analyzed using SPSS 16 software and a Chi-square statistical test based on age،, gender, and antibiotic resistance. Results: The greatest antibiotic resistance of E. coli was observed at ampicillin at 83.8%, cotrimoxazole at 65.1% and cefazolin at 68.4% followed by cefotaxime 63.3% and ceftriaxone 61.3%, while the lowest resistance was noted for imipenem at 3% and amikacin nitrofurantoin at 3.3%. Resistance to cefazolin, ceftazidime، gentamicin، cefepime، ciprofloxacin, and amikacin was significantly higher in men compared to women. The greatest resistance to ampicillin, ceftazidime, cefotaxime, ceftriaxone, cotrimoxazole antibiotics was notebly observed in the age group of 60- 41 years, while the least resistance was found in the age group of 21-40 years. Women showed significantly the  the highest resistance to cefepime in the surgical department and the lowest in the emergency department, resistance to levofloxacin was the highest in the internal ward and lowest in the infectious ward, and resistance to Nitrofurantoin in the cardiac department compared to other departments. Conclusion: The current study shows high antibiotic resistance to E. coli isolates in patients with urinary tract infections referred to the laboratory، especially in the population of men and elderly people. In order to prevent the spread of treatment resistance، urine culture should be done in patients.